2017
DOI: 10.21577/0100-4042.20170030
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da liberação de elementos traço em solos tratados com xisto retortado

Abstract: EVALUATION OF TRACE ELEMENTS RELEASING FROM SOILS TREATED WITH RETORTED OIL SHALE. Soils that had received successive applications of retorted oil shale (ROS) in an experiment under field conditions were used in this study, aiming to evaluate the availability of trace elements. In the batch tests, we observed that toxic elements present in the ROS are not desorbed from the matrix in significant amounts to contaminate soil and groundwater. The element Ca represents the greatest nutrient contribution, which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(31 reference statements)
2
2
0
Order By: Relevance
“…1(e and f) showed that the higher ROS dose (18 Mg ha À1 ) was unable to increase the soil content of barium and arsenic. These results are in agreement with those from Santos et al (2017) and Loeck (2018) which observed that the ROS can be used as a soil conditioner in agriculture without adding harmful elements to the environment.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1(e and f) showed that the higher ROS dose (18 Mg ha À1 ) was unable to increase the soil content of barium and arsenic. These results are in agreement with those from Santos et al (2017) and Loeck (2018) which observed that the ROS can be used as a soil conditioner in agriculture without adding harmful elements to the environment.…”
Section: Resultssupporting
confidence: 93%
“…This type of study can be used to access soil side-effects caused by any type of soil inputs. The evaluated amendment was retorted oil shale (ROS), whose agronomic efficiency and potential applications were properly documented previously (Santos et al, 2017;Giacomini, 2017;Giacomini, 2017), therefore, its wide use in agriculture are potentially high. The ROS is a solid by-product of the oil, natural gas, and sulphur extraction from oil shale and represents 80e90% of the feedstock weight (around 5.000 tons per day) (Petrobras, 2019;Pimentel et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…The EC in soil solution collections obtained similar values in fertilization with U and U+ROS and planting spacing. Our results corroborates those reported by Santos et al (2017) in soil extracts where successive doses of retort shale were applied under field conditions, in which they did not observe changes in EC and inferred that although with higher levels of some elements in ROS, the quantities released were not enough to cause a change in EC values.…”
Section: Resultssupporting
confidence: 92%
“…However, in the chemical composition of ROS, trace elements can indicate a potential pollutant from this residue, whose vertical transfer could imply in surface water and groundwater contamination/pollution by the leaching process, but few is known about such potential. Pereira & Vitti (2004) and Santos et al (2017) evaluated the release of metals from ROS and reported that its use did not modify the soil concentrations of toxic metal ions, pointing out the low concentration of the respective trace elements in the ROS, and, in general, the presence of ROS did not contribute to leaching and bioavailability of trace elements, maintaining these elements below threshold levels according to current legislation. However, there is still a need for further information on the leaching of chemical elements present in ROS, mainly considering the employment of ROS in a large quantity, as the continuous use in coated urea for many years.…”
Section: Introductionmentioning
confidence: 99%